2021
DOI: 10.3390/healthcare9111566
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Delta Variant: Perceptions, Worries, and Vaccine-Booster Acceptability among Healthcare Workers

Abstract: Background: As the COVID-19 Delta variant has spread across the globe, healthcare workers’ (HCWs) knowledge, worries, and vaccine booster acceptance should be assessed. Methods: Online questionnaires aimed at HCWs in Saudi Arabia were distributed between 9 and 12 August 2021, aiming to evaluate HCWs’ perceptions and worries about the Delta variant as well as their feelings about receiving a booster-vaccine. Results: A total of 1279 HCWs participated, with 51.1% being physicians and 41.7% nurses. 92.5% were awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
74
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 47 publications
17
74
2
1
Order By: Relevance
“…This study explored HCWs’ perceptions and beliefs of vaccine effectiveness and advocacy in relation to the emerging SARS-CoV-2 Omicron variant in KSA. Most respondents were females (62%), similar to a previous study about the Delta variants concern in KSA, and in agreement with other studies showing females to be the mainstream among HCWs[11,13,14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study explored HCWs’ perceptions and beliefs of vaccine effectiveness and advocacy in relation to the emerging SARS-CoV-2 Omicron variant in KSA. Most respondents were females (62%), similar to a previous study about the Delta variants concern in KSA, and in agreement with other studies showing females to be the mainstream among HCWs[11,13,14].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, almost 22% reported being previously diagnosed with laboratory-confirmed COVID-19, compared to only 9% in the beginning of vaccine rollout, but similar to that reported during the delta variant emergence. This difference could be due to the longer exposure with the lapse of time between the initial introduction of vaccines in late December 2020 and the slow but steady vaccine uptake by HCWs [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Hesitancy and willingness in relation to the COVID-19 vaccination have been investigated in different groups worldwide with a number of individuals who would either be unwilling to receive it or refuse it altogether despite the severity of the disease [8,9]. However, little is known yet about the intention to receive the booster dose [10][11][12][13][14][15][16]. In this current scenario, this is a challenging issue.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding lockdown, a previous study of the B.1.1.7 variant about 53% of surveyed HCWs in Saudi Arabia indicated the worry about lockdown if that variant reached KSA[41]. And another study the response to the worry about lockdown was only thought of if the delta variant would cause a second wave[16]. In the United Kingdom, a third lockdown was done in January 2021 to prevent excess deaths form a third wave[55].…”
Section: Discussionmentioning
confidence: 99%
“…Certain subgroups within HCWs, such as front-line and female workers, were particularly vulnerable to worse mental health outcomes[12-15]. Furthermore, a study on healthcare workers following the spread of the SARS-CoV-2 Delta variant revealed high levels of worry[16].…”
Section: Introductionmentioning
confidence: 99%